CACCI country profile Peru - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
Peru faces a variety of climate risks just like the rest of the countries in the region. Being a country rich in biodiversity and climatic variety, Peru experiences different climatic impacts, which have been increasing in severity over time. These include increased rainfall, increased periods of drought, and soil degradation, among many other effects. For this reason, Peru has implemented numerous measures to fight against the effects of climate change. These measures focus on sectors vital to the development of the country, along with industries and services that are most directly affected by climate change. Actions have utilized international and national instruments strengthened for the current climate crisis, always taking into consideration all parts of the system by carrying out inter-institutional and multilevel interventions.